Processes of identity in female police officers - Prince, Jane (Cranfield University, 1993)
Almost all studies of policewomen are concerned with strong and specific strains on the identity. The literature reviewed reveals both two social divides and two occupational divides. Theories of identity are also reviewed and these similarly separate into those concerned with socialisation and others which focus on struggles, on conflicts. Both draw attention to the social contexts and to coping strategies. From these literature based accounts a methodology is derived which brings together the quantitative and the qualitative through the use of the survey, the interview and participant observation. There were 152 respondents, 24 interview subjects and three periods of observation. The key link is to be found in the Theory of Type. There is a policewomen personality which extraverts 'sensing'; external world patterns and facts are preferred to abstract relationships. This type is in balance with the background characteristics identified. Family members encouraged joining, educational levels are higher than average and the women joined especially for job security and pay along with a value of public service. Their dislikes spread across their treatment by both men and the management structure. Their likes are for the variety and unpredictability of the work itself. The critical incident interviews deepen the understanding of the conflicts experienced, five major conflicts being identified. The responses include confrontation, a strategy previously unidentified as having the same degree of Significance as others in managing conflicts of identity. Passing and denial are much less frequently used. The longer serving and the promoted women are more likely to be confrontational in their responses to contradictions. The distinction between policewomen and policewomen was not identifiable in this sample. The greatest preference for managing contradictions and conflict was through assertion and confrontation. These data lead to the conclusion that gender identity can be a synthesis rather than a segmentation. Furthermore this synthesis may be both personal and stable and an aspect of policewomen whether on or off duty.